The unintended implications of blurring the line between research and clinical care in a genomic age. (May 2014) - Berkman, Benjamin E; Hull, Sara Chandros; Eckstein, Lisa
While the development of next-generation sequencing technology has had a paradigm-changing impact on biomedical research, there is likely to be a gap between discovery of therapeutic benefits in research and actual adoption of the new technology into clinical practice. This gap can create pressure on the research enterprise to provide individualized care more typical of the clinic setting because it is uniquely accessible in research. This blurring of the line between research and clinical care is understandable, and perhaps even inevitable. But even if the gap is only transitory, such a blurring can have lasting implications, both by expanding obligations imposed on researchers, but also by challenging long-held ethical views. We explore this idea, focusing on how the dissolving distinction between research and clinical care has influenced the vigorous debate around how researchers should manage genetic findings (sometimes separated into primary and incidental or secondary findings) resulting from research.